A multimodal brain imaging dataset on sleep deprivation in young and old humans: The Sleepy Brain Study 1, version 3 - Nilsonne, KI, Gustav (Karolinska Institutet, 2021)
The Stockholm Sleepy Brain Study I is a functional brain imaging study of 48 younger (20-30 years) and 36 older (65-75 years) healthy participants, with magnetic resonance imaging after normal sleep and partial sleep deprivation in a crossover design. We performed experiments investigating emotional mimicry, empathy for pain, and cognitive reappraisal, as well as resting state functional magnetic resonance imaging (fMRI). We also acquired T1- and T2-weighted structural images and diffusion tensor images (DTI). On the night before imaging, participants were monitored with ambulatory polysomnography and were instructed to sleep either as usual or only three hours. Participants came to the scanner the following evening. Besides MRI scanning, participants underwent behavioral tests and contributed blood samples, which have been stored in a biobank and used for DNA analyses. Participants also completed a variety of self-report measures. The resulting multimodal dataset may be useful for hypothesis generation or independent validation of effects of sleep deprivation and aging, as well as investigation of cross-sectional associations between the different outcomes.
A full description of study design and procedures is available at: https://openarchive.ki.se/xmlui/handle/10616/45181

The dataset is available for download with the tool Datalad (https://www.datalad.org/). The command after installing Datalad is:
datalad install -r https://github.com/NilsonneData/SleepyBrain1.git

Earlier versions of this dataset can be found here: https://openneuro.org/datasets/ds000201/versions/1.0.3

Stockholm Sleepy Brain-studien 1 är en funktionell hjärnavbildningsstudie av 48 yngre (20-30 år) och 36 äldre (65-75 år) friska försökspersoner, med magnetkameraundersökning utförd efter normalsömn och partiell sömnbrist i en överkorsad design. Vi utförde experiment som undersökte emotionell härmning, empati för smärta och kognitiv omtolkning, såväl som funktionell magnetkameraundersökning (fMRI) av hjärnans vilotillstånd. Vi samlade också in T1- och T2-viktade strukturella bilder och diffusionstensorbilder (DTI). Natten före magnetkameraundersökning övervakades försökspersonerna med polysomnografi och instruerades att sova som vanligt eller endast tre timmar. Försökspersonerna undersöktes nästa kväll med magnetkameran. Förutom hjärnavbildning genomgick försökspersonerna också beteendetester och lämnade blodprover som har lagrats i en biobank och använts för DNA-analyser. Deltagarna fyllde också i ett antal självskattningsformulär. Detta multimodala dataset kan användas för hypotesgenerering eller oberoende validering av effekter av sömnbrist och åldrande, såväl som undersökningar av tvärsnittssamband mellan de olika måtten.
En fullständig beskrivning av studiedesign och metoder finns på: https://openarchive.ki.se/xmlui/handle/10616/45181

Datasetet är tillgängligt att ladda ner via verktyget Datalad (https://www.datalad.org/). Installera Datalad lokalt, använd sedan kommandot:
datalad install -r https://github.com/NilsonneData/SleepyBrain1.git

Tidigare versioner av datasetet finns på https://openneuro.org/datasets/ds000201/versions/1.0.3
Data från en multimodal hjärnavbildningsstudie av yngre och äldre människor: Sleepy Brain 1-studien, version 3
Keywords: Emotions; Emotioner; Electromyography; Elektromyografi; Magnetic Resonance Imaging; Magnetisk resonanstomografi; Sleep Deprivation; Sömnbrist; Polysomnography; Sömnövervakning; Expressed Emotion; Uttryckt känsla; Diffusion Tensor Imaging; Diffusionstensoravbildning; Neurosciences; Neurovetenskaper